The relationships of religiosity, spirituality, religious and spiritual coping with depression among medical and health science students - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmad H. Osman, Rahmah; Abd. Razak, Abdul Latif; Allie, Nasreen; Ahmed, Mohamed Ayaaz; Jalaludin, Mohamad Afiudin; Mohd Kadri, Nursyuhaidah (Beijing Advanced Manufacturing Technology Consultation Center, 2022)
Introduction: Depression is a global mental health issue. Vulnerability for this condition increases in the university student population, specifically in the medical and health science disciplines. Previous evidence showed that religiosity and spirituality were inversely linked with depression. They have also been predominantly treated as one construct. Still, these relationships are vague. Objective: This study aims to investigate these correlational relationships of religiosity and spirituality with depression among medical and health sciences students. Methods: A total of 151 medical and health science students were recruited from various universities across Malaysia. Beck’s Depression Inventory second edition (BDI-II) was used to measure depression and depressive symptoms, the Duke University Religion Index (DUREL) was used to measure religiosity, and the Spirituality Scale (SS) was used to measure the beliefs, intuitions, lifestyle choices, practices, and rituals representative of the human spiritual dimension. Whilst the brief scale of religious coping (RCOPE) and spiritual coping questionnaire (SCQ) were used to assess positive and negative religious and spiritual coping respectively. Results: A negative relationship was found between religiosity, positive religious coping, and depression. Whilst positive relationship was found between negative religious coping and depression. Conclusion: These findings give insight into this population. It also provides avenues for psychoeducation and intervention. The ramifications of these findings may be applicable at the society as well as the government and policy making level in Malaysia.